Shifts in Vaginal Bacterial Community Composition Are Associated With Vaginal Mesh Exposure. Issue 11 (22nd November 2021) - Deveneau, Nicolette E.; Newton, Ryan J.; Agrawal, Anubhav; Kinman, Casey L.; Wu, Guizhu; Lei, Zhenmin; Francis, Sean L.
Abstract : Supplemental digital content is available in the text. Abstract : Objective: The objective of this study was to evaluate the relationship between vaginal mesh exposure and vaginal bacterial community composition. Methods: Vaginal swab samples were collected from 13 women undergoing excision of vaginal mesh with vaginal mesh exposure. Samples were collected at the midvagina, site of exposure, and underneath the vaginal epithelium at the exposure. Control samples were collected vaginally during 15 new patient examinations. For all samples, we extracted genomic DNA and polymerase chain reaction amplified and sequenced the 16S rRNA gene V4 region. We tested for differences in the microbiota among control and exposure samples with PERMANOVA tests of beta diversity measures (Morisita-Horn dissimilarity) and Wilcoxon rank sum tests of Lactobacillus distribution. Results: Vaginal bacterial communities in both control and case groups were divided into 2 primary community types, one characterized by Lactobacillus dominance (>50% of community) and the other by low Lactobacillus and a high diversity of vaginal anaerobes. In 10 of 13 case women, bacterial communities were highly similar between the 3 vaginal sites (adonis R 2 = 0.86, P = 0.0099). In the 3 women with community divergence, all 3 were characterized by decreased Lactobacillus abundance at the exposure site. Overall, Lactobacillus abundance was lower at the site of mesh exposure and under the epithelium than in the experimental control ( W = 137, P = 0.072, r = 0.41; W = 146, P = 0.025, r = 0.50). Common putative pathogenic mesh colonizing bacteria were common (in 51 of 54 samples), but generally not abundant (median relative abundance = 0.014%). Conclusions: In vaginal mesh exposure cases, a woman is more likely to have a diverse, non- Lactobacillus –dominant community.